Technical and environmental analysis of large-scale pig manure digestion through process simulation and life cycle assessment (2021)
The biogas and by-products production from anaerobic digestion of pig manure was evaluated technically, economically, and environmentally in an industrial park in Bogotá, Colombia, in order to generate economic opportunities and to reduce environmental impacts. Mass and energy balances were performed using data from literature and developing a simulation of the AD process in Aspen Plus software based on stoichiometric balances. The environmental evaluation of this process was developed using LCA methodology. Also, the economic viability of the process was evaluated by calculating the internal rate of return and the net present value considering 10 years of life of the plant and equipment. The results of the environmental evaluation show that the stages of transport, and consumption of electrical and thermal energy contribute to the categories of acidification, abiotic, and ozone layer depletion, for both scenarios of interest according to the allocation of the final product. Furthermore, it is established that the project is viable as it has an internal rate of return of 26% and a payback time of 5 years, according to the results of the economic evaluation.